The Establishment of Quantitatively Regulating Expression Cassette with sgRNA Targeting BIRC5 to Elucidate the Synergistic Pathway of Survivin with P-Glycoprotein in Cancer Multi-Drug Resistance - Deng, Changping; Hu, Fabiao; Zhao, Zhangting; Zhou, Yiwen; Liu, Yuping; Zhang, Tong; Li, Shihui; Zheng, Wenyun; Zhang, Wenliang; Wang, Tianwen; Ma, Xingyuan (Frontiers in Cell and Developmental Biology, 2022)
Quantitative analysis and regulating gene expression in cancer cells is an innovative method to study key genes in tumors, which conduces to analyze the biological function of the specific gene. In this study, we found the expression levels of Survivin protein (BIRC5) and P-glycoprotein (MDR1) in MCF-7/doxorubicin (DOX) cells (drug-resistant cells) were significantly higher than MCF-7 cells (wild-type cells). In order to explore the specific functions of BIRC5 gene in multi-drug resistance (MDR), a CRISPR/Cas9-mediated knocking-in tetracycline (Tet)-off regulatory system cell line was established, which enabled us to regulate the expression levels of Survivin quantitatively (clone 8 named MCF-7/Survivin was selected for further studies). Subsequently, the determination results of doxycycline-induced DOX efflux in MCF-7/Survivin cells implied that Survivin expression level was opposite to DOX accumulation in the cells. For example, when Survivin expression was down-regulated, DOX accumulation inside the MCF-7/Survivin cells was up-regulated, inducing strong apoptosis of cells (reversal index 118.07) by weakening the release of intracellular drug from MCF-7/Survivin cells. Also, down-regulation of Survivin resulted in reduced phosphorylation of PI3K, Akt, and mTOR in MCF-7/Survivin cells and significantly decreased P-gp expression. Previous studies had shown that PI3K/Akt/mTOR could regulate P-gp expression. Therefore, we speculated that Survivin might affect the expression of P-gp through PI3K/Akt/mTOR pathway. In summary, this quantitative method is not only valuable for studying the gene itself, but also can better analyze the biological phenomena related to it.